Effect of Nitric Acid Concentrations on Synthesis and Stability of Maghemite Nanoparticles Suspension - Irwan Nurdin; Mohd Rafie Johan; Iskandar Idris Yaacob; Bee Chin Ang (The Scientific World Journal)
Maghemite (γ-Fe2O3) nanoparticles have been synthesized using a chemical coprecipitation method at different nitric acid concentrations as an oxidizing agent. Characterization of all samples performed by several techniques including X-ray diffraction (XRD), transmission electron microscopy (TEM), alternating gradient magnetometry (AGM), thermogravimetric analysis (TGA), dynamic light scattering (DLS), and zeta potential. The XRD patterns confirmed that the particles were maghemite. The crystallite size of all samples decreases with the increasing concentration of nitric acid. TEM observation showed that the particles have spherical morphology with narrow particle size distribution. The particles showed superparamagnetic behavior with decreased magnetization values at the increasing concentration of nitric acid. TGA measurement showed that the stability temperature decreases with the increasing concentration of nitric acid. DLS measurement showed that the hydrodynamic particle sizes decrease with the increasing concentration of nitric acid. Zeta potential values show a decrease with the increasing concentration of nitric acid. The increasing concentration of nitric acid in synthesis of maghemite nanoparticles produced smaller size particles, lower magnetization, better thermal stability, and more stable maghemite nanoparticles suspension.